Some Aspects of a School Life of Elder Teenagers - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 2004)
First of all, the article reveals the importance of a school life as an integral factor of education in upbringing person’s spirituality. Then the concept of a school life is given. It is the activity and communication processes that take place in school community and are closely with the needs, interests and experiences of members of the school community. Naming emotional states as the corresponding dimensions of a school life, the peculiarities of self-feeling and anxiety of elder pupils are character razed. A concrete data of the research reveals how these pupils usually feel in their class, whether they feel happy, what they lack and what causes their anxiety. The data shows that the causes of anxiety of pupils are fear not to fulfil the expectations of their nearest relatives, self-expression fear, fear in general and fear of the knowledge check. This data is pretty much the same according to the sex and the type of a school (whether the pupils study at a secondary school or at a gymnasium).